Association of temporomandibular joint space and condylar head position with different skeletal patterns among the Malaysian population - Khalid, Rafiq; Ismail, Izzati Nabilah; Cheong, Joo Ming; Mohd Ali, Azrul Safuan; W Mustapha, Wan Irfan (IIUM Press, 2024)
During growth and development of the head and neck, some degree of interaction and interdependence between skeletal pattern with temporomandibular joint (TMJ) space and condylar head position occurs. Results from previous studies are varied; some reporting significant difference of TMJ space or condylar head position among the skeletal patterns, whilst others have shown that no such association is present. Considering that previous studies have been conducted in populations outside of Malaysia and the importance of determining the correlation between skeletal and TMJ morphology, this retrospective study was done to evaluate the TMJ space and condylar head position in different skeletal patterns among the Malaysian population using computed tomography (CT) images. A total of 90 CT images of the head and neck were included. Skeletal pattern (class I, II, III) was determined from each CT image based on the ANB angles obtained from reconstruction of these images. The TMJ space measurement and condylar head position were determined from sagittal images based on established landmarks from the reconstructed CT images. Statistical analysis was used to compare the TMJ space and condylar head position across the three skeletal classes and assess its significance. The results of this study demonstrated that there was no significant association between TMJ space or condylar head position in the different skeletal patterns among the Malaysian population. It is recommended that a prospective study with large sample size and standardized measurement techniques be implemented in the future to determine the precise association between TMJ morphology and different skeletal patterns.